Mechanical, chemical resistance and morphological properties of epoxidized natural rubber toughened polylactic acid blends - Nurhayati Ahmad Zawawi, 1986-; Azman Hassan, supervisor; Mat Uzir Wahit, supervisor; Fakulti Kejuruteraan Kimia (2010)
Thesis (Sarjana Sains (Teknologi Polimer)) - Universiti Teknologi Malaysia, 2010